2022
DOI: 10.1021/acs.chemmater.2c02993
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Construction of Single-Site Ti Active Centers on Carbon Nitride for Photocatalytic Chemoselective Hydrogen Transfer Reduction

Abstract: In this work, we report an in situ construction of single-site Ti active centers on a carbon nitride surface during photocatalytic processes for one-pot chemoselective hydrogen transfer reduction of nitroaromatics and domino-type reaction using Cp2TiCl2 and −OH-enriched carbon nitride (OHCN) as precatalysts. Due to the selective adsorption of nitro and the promotion of photogenerated charge transfer by single-site Ti active species and the formation of Ti3+, the system can achieve an efficient chemoselective r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…These results can be confirmed by X-ray diffraction (XRD) characterization (Figure S11). The XRD patterns of Co 0.5 /Cu 0.5 -bpy/CNHS, Co 1.0 -bpy/CNHS, and Cu 2.0 -bpy/CNHS show the characteristic diffraction peaks attributed to carbon nitride but no diffraction peaks of Co and Cu-related nanoparticles and clusters. In addition, we tested the EDX spectrum (Figure S12) and C, N, Co, and Cu element mapping of Co 0.5 /Cu 0.5 -CNHS (Figure b–f).…”
Section: Results and Discussionmentioning
confidence: 97%
“…These results can be confirmed by X-ray diffraction (XRD) characterization (Figure S11). The XRD patterns of Co 0.5 /Cu 0.5 -bpy/CNHS, Co 1.0 -bpy/CNHS, and Cu 2.0 -bpy/CNHS show the characteristic diffraction peaks attributed to carbon nitride but no diffraction peaks of Co and Cu-related nanoparticles and clusters. In addition, we tested the EDX spectrum (Figure S12) and C, N, Co, and Cu element mapping of Co 0.5 /Cu 0.5 -CNHS (Figure b–f).…”
Section: Results and Discussionmentioning
confidence: 97%
“…The research group of Gao and Gu reported a chemoselective hydrogen transfer reduction of nitroaromatics and a domino-type reaction over the composite (OHCN-Ti) of Cp 2 TiCl 2 and –OH-enriched carbon nitride (OHCN) in the mixed solvent of water and isopropanol (Scheme 4E). 68 Various nitroaromatics with different functional groups such as olefins, alkynes, ketones, imines, and haloaromatics are tolerated in this catalytic system with nitro groups reduced to amines. The remarkable chemoselectivity observed in this reaction was likely due to the preferential coordination ability of oxyphilic titanium with nitro functionality.…”
Section: Water As a Solvent Or Cosolventmentioning
confidence: 99%
“…327 Zhang et al managed to apply the first non-noble SAC for hydrogen transfer reduction. 559 By utilizing –OH enriched carbon nitrides (OHCN), the authors stabilized Cp 2 TiCl 2 leading to the formation of Ti single-sites Ti/OHCN-g. This catalyst was applied to selectively reduce several nitroaromatics.…”
Section: Catalytic Applicationsmentioning
confidence: 99%
“…The authors tested a broad scope (38 substrates) and reported successful results, with no yield lower than 78%, demonstrating the robustness of this system. 559…”
Section: Catalytic Applicationsmentioning
confidence: 99%